KONFLIK BERSENJATA DI WILAYAH UKRAINA TAHUN 2014 MENURUT HUKUM HUMANITER INTERNASIONAL - Mirsa Prajodi; Handojo Leksono; Ayub Torry Satrio Kusumo (BELLI AC PACIS, 2015)
War is one way to solve a problem from one country to another, and therefore the need for a rule that governs the war. Countries in antiquity had the rule of law governing the rules of war, but only limited in terms of fighting and different for each country. Starting from this it was made a universal rule that governs not only how to fight but from the beginning of the war, the procedure of the war, the setting of a weapon, to the treatment of civilians and prisoners of war. So from that emerging international humanitarian law governing matters more complex than an armed conflict. International humanitarian law also regulates the types of conflict and there are two types of fundamental conflict governed by international humanitarian law, namely international armed conflict and non-international armed conflict. The ongoing conflicts and interesting that the crisis in Ukraine. Conflicts arising from the desire Lugansk and Donbass city folk to liberate themselves from the Ukraine were assisted by Russia. Small demonstration was later developed, including the emergence of pro-Russian separatist movements in the eastern region of Ukraine. Ukrainian crisis of instability in the country which was originally grown increasingly worse until NATO down to secure the armed conflict.